Daunorubicin-Loaded DNA Origami Nanostructures Circumvent Drug Resistance Mechanisms in a Leukemia Model - Halley, Patrick D. (Small, 2015)
Many cancers show primary or acquired drug resistance due to the overexpression of efflux pumps. A novel mechanism to circumvent this is to integrate drugs, such as anthracycline antibiotics, with nanoparticle delivery vehicles that can bypass intrinsic tumor drug-resistance mechanisms. DNA nanoparticles serve as an efficient binding platform for intercalating drugs (e.g. anthracyclines doxorubicin and daunorubicin, which are widely used to treat acute leukemias) and enable precise structure design and chemical modifications, for example for incorporating targeting capabilities. Here, we utilize DNA nanostructures to circumvent daunorubicin drug resistance at clinically relevant doses in a leukemia cell line model. We report the fabrication of a rod-like DNA origami drug carrier that can be controllably loaded with daunorubicin. We further directly verify that nanostructure-mediated daunorubicin delivery leads to increased drug entry and retention in cells relative to free daunorubicin at equal concentrations, which yields significantly enhanced drug efficacy. Our results indicate that DNA origami nanostructures can circumvent efflux pump-mediated drug resistance in leukemia cells at clinically relevant drug concentrations and provide a robust DNA nanostructure design that could be implemented in a wide range of cellular applications due to its remarkably fast self-assembly (~5 minutes) and excellent stability in cell culture conditions.